The Effect of Ginkgo biloba Extracts on Candida albicans Isolated from Healthy Persons - Zahraa S. Qasim (College of Pharmacy University of Baghdad, 2020)
The objective was to study the effect of prepared ginkgo biloba extracts against Candida albicans isolated from healthy persons. Conducting susceptibility test, biofilm formation test, phytochemical screening test, and antioxidant activity test. One hundred oral swabs sample were obtained from healthy persons with oral lesion attending dentistry teaching hospital in dentistry college, their age ranged from 1-30 years of both sexex. The studied samples collected through 8 months (April - December / 2018). This study included two different types of ginkgo bilola extracts were prepared as aqueous and ethanolic extracts. Many tests were used, which included isolation and identification of C.albicans, conduct susceptibility test, biofilm formation test, phytochemical screening test, and antioxidant activity test for both aqueous and ethanol ginkgo biloba extracts. From 100 healthy person involved in this study, there were 21(21%) C. albicans isolates revealed from clinical specimens. Aqueous and ethanol ginkgo biloba extracts were used to study their effects against C.albicans. Zone of inhibition was higher in ethanol than aqueous extracts. Three 3 (15%) isolates showed positive biofilm formation in tube method, phytochemical reaction in ethanol extract showed 5 phytochemical compounds, while aqueous extract showed 4 phytochemical compounds, in addition to antioxidant activity in ethanol extract was higher than aqueous. In conclusion C. albicans is the only species from genus Candida isolated from oral lesion in this study, ethanol ginkgo biloba extract have a good antifungal activity, higher number of phytochemical compounds and a higher antioxidant activity than aqueous extract.